Admixture mapping of ankle-arm index: identification of a candidate locus associated with peripheral arterial disease. - Scherer, M L; Nalls, M A; Pawlikowska, L; Ziv, E; Mitchell, G; Huntsman, S; Hu, D; Sutton-Tyrrell, K; Lakatta, E G; Hsueh, W-C; Newman, A B; Tandon, A; et al. (J Med Genet, 2010)
BACKGROUND: Peripheral arterial disease (PAD) is associated with significant morbidity and mortality, and has a higher prevalence in African Americans than Caucasians. Ankle-arm index (AAI) is the ratio of systolic blood pressure in the leg to that in the arm, and, when low, is a marker of PAD. METHODS: The authors used an admixture mapping approach to search for genetic loci associated with low AAI. Using data from 1040 African American participants in the observational, population based Health, Aging, and Body Composition Study who were genotyped at 1322 single nucleotide polymorphisms (SNPs) that are informative for African versus European ancestry and span the entire genome, we estimated genetic ancestry in each chromosomal region and then tested the association between AAI and genetic ancestry at each locus. RESULTS: The authors found a region of chromosome 11 that reaches its peak between 80 and 82 Mb associated with low AAI (p<0.001 for rs12289502 and rs9665943, both within this region). 753 African American participants in the observational, population based Cardiovascular Health Study were genotyped at rs9665943 to test the reproducibility of this association, and this association was also statistically significant (odds ratio (OR) for homozygous African genotype 1.59, 95% confidence interval (CI) 1.12 to 2.27). Another candidate SNP (rs1042602) in the same genomic region was tested in both populations, and was also found to be significantly associated with low AAI in both populations (OR for homozygous African genotype 1.89, 95% CI 1.29 to 2.76). CONCLUSION: This study identifies a novel region of chromosome 11 representing an area with a potential candidate gene associated with PAD in African Americans.
Keywords: African Americans; Aged; Ankle Brachial Index; Chromosome Mapping; Chromosomes, Human, Pair 11; Female; Genetic Loci; Genotype; Humans; Male; Odds Ratio; Peripheral Vascular Diseases; Polymorphism, Single Nucleotide

Development and validation of an ankle brachial index risk model for the prediction of cardiovascular events. - Fowkes, F G R; Murray, G D; Butcher, I; Folsom, A R; Hirsch, A T; Couper, D J; deBacker, G; Kornitzer, M; Newman, A B; Sutton-Tyrrell, K C; Cushman, M; Lee, A J; et al. (Eur J Prev Cardiol, 2014)
BACKGROUND: The ankle brachial index (ABI) is related to risk of cardiovascular events independent of the Framingham risk score (FRS). The aim of this study was to develop and evaluate a risk model for cardiovascular events incorporating the ABI and FRS. DESIGN: An analysis of participant data from 18 cohorts in which 24,375 men and 20,377 women free of coronary heart disease had ABI measured and were followed up for events. METHODS: Subjects were divided into a development and internal validation dataset and an external validation dataset. Two models, comprising FRS and FRS + ABI, were fitted for the primary outcome of major coronary events. RESULTS: In predicting events in the external validation dataset, C-index for the FRS was 0.672 (95% CI 0.599 to 0.737) in men and 0.578 (95% CI 0.492 to 0.661) in women. The FRS + ABI led to a small increase in C-index in men to 0.685 (95% CI 0.612 to 0.749) and large increase in women to 0.690 (95% CI 0.605 to 0.764) with net reclassification improvement (NRI) of 4.3% (95% CI 0.0 to 7.6%, p = 0.050) and 9.6% (95% CI 6.1 to 16.4%, p < 0.001), respectively. Restricting the FRS + ABI model to those with FRS intermediate 10-year risk of 10 to 19% resulted in higher NRI of 15.9% (95% CI 6.1 to 20.6%, p < 0.001) in men and 23.3% (95% CI 13.8 to 62.5%, p = 0.002) in women. However, incorporating ABI in an improved newly fitted risk factor model had a nonsignificant effect: NRI 2.0% (95% CI 2.3 to 4.2%, p = 0.567) in men and 1.1% (95% CI 1.9 to 4.0%, p = 0.483) in women. CONCLUSIONS: An ABI risk model may improve prediction especially in individuals at intermediate risk and when performance of the base risk factor model is modest.
Keywords: Adult; Aged; Aged, 80 and over; Ankle Brachial Index; Cardiovascular Diseases; Europe; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Prognosis; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States; Young Adult